The contemporary significance of the moral economy: Is housing a home or an asset?. (June 2018) - Susser, Ida
This Afterword reviews the diversity of moral economies of housing under the current neoliberal regime. Based on the articles in this theme issue, it considers the ways people's relationships to their housing have changed as the economy has shifted from a welfare state centered on industrial workers to a financialized economy more reliant on precarious occupations. In the process, the article suggests that struggles over homes and housing have framed the emergence of social movements, both from the left and from the right.